Association of progressive intracranial necrotic lesion with acute myelogenous leukemia: A case report - Marutani, Akiko; Asada, Kiyokazu; Nishi, Noriyuki; Yamada, Tomonori (Indian Journal of Case Reports, 2018)
For patients with acute myelogenous leukemia (AML) and invasive central nervous system lesions, there are many possible differential diagnoses, including collagen diseases, infectious diseases, drug reactions or side effects, and vascular diseases. Herein, we describe the clinical course, diagnostic examinations, and treatment outcomes for a patient with AML complicated by a progressively enlarging intracranial necrotic lesion. As no tumor cells were seen on microscopic examination, and since the clinical symptoms improved after leukemia therapy, myeloid sarcoma was highly suspected. Taken together, this case suggests that a combination of the clinical course, radiological findings, and treatment history should be considered to eliminate other possible diagnoses.